FUNGSI AFEKTIF KELUARGA DAN FUNGSI SOSIALISASI KELUARGA DENGAN PERILAKU SEKSUAL REMAJA - Pattiruhu, Immanuel Chandra Supit; Rompas, Sefti; Simak, Valen (JURNAL KEPERAWATAN, 2019)
Abstract: Sexual behavior is risky behavior that aims to attract the attention of the opposite sex which involves touching physical limbs between men and women who have reached intimate relationships. Family functions that are not good can affect adolescent sexual behavior. Therefore, the affective function of the family and family socialization functions play a special role in adolescent growth and development. The aim of this research was to determine the corelation between family affective function and family socialization function with adolescent sexual behavior in SMK Negeri 1 Manado. The research design used descriptive analysis with a cross sectional study approach. This research involved312 respondents obtained by using the Simple Random Sampling technique. The results of the statistical test using Chi-square test at a significance level of 95%, obtained a significant value Ï = 0,000 <Î± (0,05) for affective function of family with sexual behavior in adolescent andÏ = 0,000 <Î± (0,05)for socialization function of family with sexual behavior in adolescent. Conclusion there is a corelation between family affective function with adolescent sexual behavior and there is a corelation between family socialization function with adolescent sexual behavior.Keywords : Affective Function, Function of Socialization, Adolescent, Sexual BehaviorAbstrak : Perilaku seksual merupakan perilaku beresiko yang bertujuan untuk menarik perhatian lawan jenis yang melibatkan sentuhan secara fisik anggota badan antara pria dan wanita yang telah mencapai pada hubungan intim. Fungsi keluarga yang tidak baik dapat mempengaruhi perilaku seksual remaja. Oleh karena itu, fungsi afektif keluarga dan fungsi sosialisasi keluarga sangat berperan khusus dalam tumbuh kembang remaja. Tujuan untuk mengetahui hubungan fungsi afektif keluarga dan fungsi sosialisasi keluarga dengan perilaku seksual remaja di SMK Negeri 1 Manado. Desain penelitian yang digunakan yaitu Deskriptif Analitik dengan pendekatan Cross Sectional Study. Sampel berjumlah 312 responden yang didapat dengan menggunakan tehnik Simple Random Sampling. Hasil penelitian uji statistic menggunakan uji Chi-square pada tingkat kemaknaan 95%, didapatkan nilai signifikan Ï = 0,000 < Î± (0,05) untuk Fungsi Afektif keluarga dengan perilaku seksual remaja dan Ï = 0,000 < Î± (0,05) untuk Fungsi Sosialisasi keluarga dengan perilaku seksual remaja. Kesimpulan ada hubungan antara fungsi afektif keluarga dengan perilaku seksual remaja dan ada hubungan antara fungsi sosialisasi keluarga dengan perilaku seksual remaja.Kata kunci : Fungsi Afektif, Fungsi Sosialisasi, Perilaku Seksual, Remaja